High expression of B4GALT1 is associated with poor prognosis in acute myeloid leukemia - Ren, Zhihong; Huang, Xiaoyu; Lv, Qing; Lei, Yiming; Shi, Haiqiang; Wang, Fanping; Wang, Mingyong (Frontiers in Genetics, 2022)
Acute myeloid leukemia is the most prevalent type of leukemia in adults and is prone to relapse and chemoresistance, with a low long-term survival rate. Therefore, the identification of quality biomarkers constitutes an urgent unmet need. High expression of beta-1,4-galactosyltransferase 1 (B4GALT1) has been observed in several cancer types; however, its function in acute myeloid leukemia has been rarely reported. Therefore, in our study, we obtained gene expression data from The Cancer Genome Atlas (TCGA) database to analyze the relationship between B4GALT1 and AML. We compared the expression of B4GALT1 in LAML and healthy samples using the Wilcoxon rank-sum test. Furthermore, the association between B4GALT1 and survival rates was investigated using Kaplan-Meier analysis and Cox regression. The nomogram obtained by Cox analysis predicts the effect of B4GALT1 on the prognosis. To assess the enrichment pathway and function of B4GALT1-related genes and the correlation between B4GALT1 and immune features, GO/KEGG, protein-protein interaction network, and single sample gene set enrichment analysis were used. The results showed that B4GALT1 is overexpressed in LAML and has some reference value in the diagnostic and prognostic assessment of LAML. Moreover, functional enrichment showed that B4GALT1 and its 63 associated genes were closely associated with the negative regulation of the apoptotic signaling pathway. In addition, B4GALT1 expression was positively correlated with the infiltration levels of macrophages, regulatory T cells (Tregs), and Th17 cells; in contrast, B4GALT1 expression was negatively correlated with the infiltration levels of T helper cells, Mast cells, and NK cells. In conclusion, our research shows that B4GALT1 may play a vital role in the occurrence of AML.